First principles study on do half-metallic properties of full-Heusler compounds RbCaX2 （X = C, N, and O） - 高永春 王啸天 Habib Rozale (中国物理B：英文版, 2015)
A first-principles approach is employed to study the structural, electronic, and magnetic properties of RbCaX2 （X = C, N, and O） full-Heusler compounds. It is observed that RbCaN2 and RbCaO2 are new do half-metals with an integer magnetic moment of 3 μB and 1 μB in their ferrimagnetic ground states, respectively, while RbCaC2 is a common metallic compound. Analysis of the density of states of these compounds indicates that the magnetic moment and furthermore, the half-metallicity primarily originate from the spin-polarization of the p-like states of N and O atoms. The half-metallic （HM） gaps of RbCaN2 and RbCaO2 are notably large; thus, the half-metallicity is robust against lattice distortion. Such materials are suitable to be grown on various semiconductor substrates. In addition, for RbCaN2 and RbCaO2, four possible terminations of the surface are also calculated.